POLITICAL FIQH DURING THE COVID-19 PANDEMIC: Religiosity and Mosque Congregant Health in Jombang - Moh. Makmun (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2020)
This paper aims at investigating the view of mosque boards (takmir) in Jombang on the Coronavirus Disease (Covid-19) pandemic, the strategy of mosque boards in enlivening mosques and the attitude of the mosque’s board towards the prohibition of worship in mosques during the pandemic of Covid-19. This paper presents the result of field research applying comparative approach. In analyzing data, it applies data reduction, data display, and verification. The result shows that the view of mosque boards on the Covid-19 pandemic is to be calm, not panic, and follow the government recommendations. The strategy of mosque boards in enlivening mosques during the Covid-19 pandemic encompasses socialization to congregations about Covid-19, spraying mosques with disinfectant liquid, implementing health protocols to prevent the spread of Covid-19, performing only five daily prayers and Friday prayers. Mosque boards choose to keep performing worship at mosques, but with very strict terms and conditions so that they can break the chain of the Covid-19 spread and perform prayers in congregation at the same time.[Artikel ini mendiskusikan pandangan takmir masjid di Kabupaten Jombang tentang Corona Virus Disease 2019 (Covid-19), strategi takmir masjid memakmurkan masjid, dan sikap takmir masjid atas larangan ibadah di masjid pada masa Covid-19. Artikel ini merupakan hasil penelitian lapangan dengan pendekatan komparatif. Proses analisis data dilakukan dengan cara reduksi data, display data, dan penarikan kesimpulan atau verifikasi. Artikel ini menyimpulkan pandangan takmir masjid tentang Covid-19 adalah bersikap tenang, tidak panik, dan mengikuti anjuran pemerintah. Strategi takmir masjid dalam mencegah penyebaran Covid-19 adalah: sosialisasi seputar Covid-19, menyemprotkan cairan disinfektan di masjid, menerapkan protokol kesehatan terhadap pencegahan penyebaran Covid-19, hanya melaksanakan salat lima waktu dan salat Jumat, tetap mengadakan ibadah di masjid dengan syarat dan ketentuan yang ketat, sehingga bisa memutus mata rantai penyebaran Covid-19 sekaligus bisa beribadah bersama dengan sempurna]